“...These events have their representatives of supporters in almost all villages of the region.” Doc-uments and materials about the Baksan events of 1928 in Kabardino-Balkaria - Kasbolat Fitsevich Dzamikhov; Artur Gusmanovich Kazharov; Karina Aslanovna Kushkhova (Кавказология, 2023)
The article is devoted to the study of the historical causes and prerequisites of the tragic events that occurred in the Baksan district of the Kabardino-Balkarian Autonomous Region in June 1928 and went down in history as the “Baksan events”. This was the first, open and large-scale protest of a part of the Kabardian peasantry against the policies of the Soviet government in the economic, social and cultural-ideological spheres.The Soviet model of modernization of all aspects of life and activity of Kabardino-Balkarian society meant a break with the traditional ideas of the peoples of Kabardino-Balkaria, which objectively led to the accumulation of conflict potential in relations between various subjects of the political process. As a result, in the late 1920s. There is an open armed confrontation, during which many people died and were injured.The causes and prerequisites, course and character, driving forces, results and consequences of the Baksan events of 1928 have still not received proper in-depth and unbiased research on regional historiography. Published documents and materials should contribute to a deep and objective study of all aspects of the history of the Baksan events, which is of great scientific importance.